Penerapan Pembelajaran Aktif Tipe Everyone Is A Teacher Here (ETH) Untuk Meningkatkan Hasil belajar Fisika Peserta Didik Kelas XA SMA Al Bayan Makassar - Muhammad Amin Said; Nirmayanti Nirmayanti; Nurlina, S. SI., M.Pd (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
This has pra ekperiment research with one –group-pretest-posttest-design with almed (1) to finding out how large learning phsics classroom XA at SMA Al Bayan Makassar in 2014/2015 before teaching with learning Active thype Everyone Is A Teacher Here (ETH) (2) to finding out how large learning phsics classroom XA at SMA Al Bayan Makassar in 2014/2015 after teaching with learning Active thype Everyone Is A Teacher Here (ETH) (3) To finding out how increases to learn before and after physics teaching with learning activ Type Everyone Is A Teacher Here (ETH). Subject in this research XA classroom. The data were collected by test learning here consist 27 item item in multiple choise had been validation by two validator. The collected data were analysx were use descriptive tecnique analysis and gain analysis. From descriptive analysis were teacing with Activ Teaching ETH type. Were collected the higest score 78. Lower score 22, average score 43 and deviation standar 14,07. Now analysis were after teaching used Aktuv type ETH were result the higest 96, lower 48, and average 75 and deviation standar 11,75. This inferensisl analiysis showed that learning phisics at XA clasroom at SMA Al bayan Makassar in 2014/2015 were increasing. Keywords : learning outcomes , Active Learning, ETH.